Landslide vulnerability analysis Sarwodadi Village, Pejawaran District Banjarnegara Regency with scoring methods - Saputra, Gaizka Tri; Azizi, Amris; Salim, M. Agus (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Sarwodadi Village is one of the villages in Pejawaran District which is an area that has a high vulnerability to landslides. This study aims to determine the level of landslide vulnerability in Sarwodadi Village, Pejawaran District, Banjarnegara Regency. Methods: The data obtained is in the form of secondary data from related agencies. Data analysis was carried out aiming to determine the classification of the level of vulnerability to landslides. Findings: From the results of data analysis carried out using the scoring method which refers to the classification from Soil and Agro-climate Research/Pusat Penelitian Tanah dan Agroklimat (Puslittanak) it can be obtained the level of landslide vulnerability, point 1 enters the low class, point 2 enters the medium class, and point 3 enters the high class against disasters landslide. Conclusion: This research reveals that Sarwodadi Village has varying levels of vulnerability to landslides based on the scoring method. Point 1 is in the low vulnerability category, point 2 is in the medium vulnerability category, and point 3 is classified as having high vulnerability. These results provide a deeper understanding of the distribution of landslide vulnerability levels in the region, which can be the basis for more effective disaster mitigation planning. Novelty/Originality: This research offers a new contribution by integrating a scoring method based on classification from Soil and Agroclimate Research to evaluate the level of landslide vulnerability at a local scale. This approach allows detailed identification of vulnerabilities at specific points, providing important empirical data for risk mitigation planning in Sarwodadi Village. This area has not been studied much before in this context.